Nanorod aspect ratios determined by the nano-impact technique - Plowman, B; Young, N; Batchelor-McAuley, C; Compton, R (Wiley, 2016)
We report the in situ electrochemical sizing of individual gold nanorods. Through the combination of electrochemical dissolution and the use of a surface-bound redox tag the volume and surface area of the nanorods are measured, and provide the aspect ratio and the size of the nanorods. Excellent independent agreement is found with electron microscopy analysis of the nanorods, establishing the application of nanoimpact experiments for the sizing of anisotropic nanomaterials.